A Solution Generator Algorithm for Decision Making based Automated Negotiation in the Construction Domain - Mahmoud, Moamin; Ahmad, Mohd Sharifuddin; Idrus, Arazi; Yahya, Azani; Husen, Hapsa (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2021)
In this paper, we present our work-in-progress of a proposed framework for automated negotiation in the construction domain. The proposed framework enables software agents to conduct negotiations and autonomously make value-based decisions. The framework consists of three main components which are, solution generator algorithm, negotiation algorithm, and conflict resolution algorithm. This paper extends the discussion on the solution generator algorithm that enables software agents to generate solutions and rank them from 1st to nth solution for the negotiation stage of the operation. The solution generator algorithm consists of three steps which are, review solutions, rank solutions, and form ranked solutions. For validation purpose, we present a scenario that utilizes the proposed algorithm to rank solutions. The validation shows that the algorithm is promising, however, it also highlights the conflict between different parties that needs further negotiation action.
Keywords: multi-agent systems; intelligent agents; value management; automated negotiation; IJIMAI